Dental auxiliary hepatitis B immunization: a cross-sectional study in the Sao Paulo state public health system, Brazil, 2018 - Saliba Garbin, Clea Adas [UNESP]; Tosta Vanzo, Ketlin Lara [UNESP]; Saliba Moimaz, Suzely Adas [UNESP]; Isper Garbin, Artenio Jose [UNESP]; Chiba, Fernando Yamamoto [UNESP] (Ministerio Da Saude, 2020)
Objective: to investigate dental auxiliaries (DA) hepatitis B immunization in Brazilian National Health System (SUS) services in nine cities in Sao Paulo State, Brazil, in 2018. Methods: this was a cross-sectional study based on interviews using a questionnaire as well as evaluation of immunity using the anti-HBs test, evaluation of prior testing, test result and interpretation and guidance provided about hepatitis B. Results: of the 70 registered DA, 35 completed the course of vaccinations, 29 had negative anti-HBs test results, 16 had tested previously, and 43 did not correctly understand their result; there was association (p=0.025) between completed course of vaccinations and receipt of guidance. Conclusion: most DA received guidance about hepatitis B; however, a considerable portion did not complete the course of vaccinations and had negative anti-HBs test results; few DA had tested previously nor correctly interpreted the result; evidence was found of an alarming scenario in which there are severe shortcomings in DA hepatitis B immunization.
Keywords: Cross-Sectional Studies; Occupational Health; Hepatitis B; Immunization; Dental Auxiliaries; Accidents; Occupational